Perbandingan Metode Pengumpulan Data dalam Penelitian Kualitatif dan Kuantitatif dalam Arahan Ilmu Akuntansi - Muammar Khaddafi; Linda Puji Kusuma; Liza Ulfitri; Tassya Putri Azzahra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the accounting discipline, the choice of data collection method is crucial because it directly impacts the validity and reliability of research results. This study aims to compare data collection methods used in qualitative and quantitative approaches and examine their relevance in the context of contemporary accounting studies. Qualitative approaches emphasize in-depth exploration of accounting phenomena, particularly those related to human behavior, perception, and decision-making processes. Common techniques used in this approach include in-depth interviews, participant observation, and case studies, which enable researchers to understand the social and organizational context behind accounting practices. In contrast, quantitative approaches prioritize collecting numerical data that can be analyzed statistically. These methods typically use instruments such as questionnaires, surveys, and experiments to objectively test pre-formulated hypotheses. Results from quantitative approaches often provide broader generalizations, but can lose the nuances of social context gained from qualitative approaches. A comparison of these two methods reveals that each has its own advantages and limitations. Qualitative approaches excel in understanding processes and meanings, while quantitative approaches are strong in producing generalizable data. Therefore, in practice, accounting researchers often adopt a mixed methods approach to gain a more comprehensive understanding. This study concludes that a thorough understanding of the characteristics of both approaches is crucial for researchers to select appropriate data collection strategies. Thus, research can make a significant contribution to the development of accounting theory and practice in a more comprehensive and meaningful way.